Concurrent agreement between an anthropometric model to predict thigh volume and dual-energy X-Ray absorptiometry assessment in female volleyball players aged 14-18 years - Tavares, Óscar M.; Valente-dos-Santos, João; Duarte, João P.; Póvoas, Susana C.; Gobbo, Luís A. [UNESP]; Fernandes, Rômulo A. [UNESP]; Marinho, Daniel A.; Casanova, José M.; Sherar, Lauren B.; Courteix, Daniel; Coelho-e-Silva, Manuel J. (Springer Nature, 2016)
Background: A variety of performance outputs are strongly determined by lower limbs volume and composition in children and adolescents. The current study aimed to examine the validity of thigh volume (TV) estimated by anthropometry in late adolescent female volleyball players. Dual-energy X-ray absorptiometry (DXA) measures were used as the reference method. Methods: Total and regional body composition was assessed with a Lunar DPX NT/Pro/MD+/Duo/Bravo scanner in a cross-sectional sample of 42 Portuguese female volleyball players aged 14-18 years (165.2 ± 0.9 cm; 61.1 ± 1.4 kg). TV was estimated with the reference method (TV-DXA) and with the anthropometric method (TV-ANTH). Agreement between procedures was assessed with Deming regression. The analysis also considered a calibration of the anthropometric approach. Results: The equation that best predicted TV-DXA was: -0.899 + 0.876 × log10 (body mass) + 0.113 × log10 (TV-ANTH). This new model (NM) was validated using the predicted residual sum of squares (PRESS) method (R2 PRESS = 0.838). Correlation between the reference method and the NM was 0.934 (95%CI: 0.880-0.964, Sy·x = 0.325 L). Conclusions: A new and accurate anthropometric method to estimate TV in adolescent female volleyball players was obtained from the equation of Jones and Pearson alongside with adjustments for body mass.
Keywords: Adolescent female athletes; Body composition; Deming regression; PRESS